Molecular phylogenetics and generic concepts in the Maxillarieae (Orchidaceae) - Williams, Norris H. (Universidad de Costa Rica, 2016)
Tribe Maxillarieae account for approximately 10% (>2800 species) of Orchidaceae and are a major com- ponent of the Neotropical epiphytic flora. Pollination systems include 1) male euglossine-bee fragrance rewards in four subtribes, 2) oil reward systems and mimicry in some groups, 3) nectar rewards in a wide range of taxa, and 4) pseudocopulation in some Maxillariinae and some Oncidiinae.